A case study on the evaluation of the guidance and counseling programs in a private sectarian school for boys - Sta. Maria, Lei Mitchen M.; De Jesus, Hildegard Y.; Lim, Christopher Andrew T.; Garcia, John Addy S. (2005)
This case study is about the program evaluation of the guidance and counseling program of an exclusive school for boys in Mandaluyong City. The purpose of this study is to determine how the institution conducts a program evaluation and the impact that it created for the program itself and the actors involved. The respondents comprise of a principal, guidance counselors, n adviser, and a group of high school students. Interviews were utilized for data gathering. The files provided by the school also helped in the gathering information and verification of data. Findings show that program evaluation provided relevant information for review and improvement of guidance and counseling practice and services.
Keywords: Counseling in secondary education -- Evaluation; Educational evaluation; Educational counseling